Strengthening Human Rights Through Community Empowerment in Law Enforcement - Sugeng Dwiono; Iskandar; Didiek R Mawardi; Azzahra Rizki Ananda; Lidia Olga (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
The approach used in this service is a participatory and collaborative approach involving various parties such as the community, law enforcement officials, NGOs, and other related agencies. Service is carried out through a series of activities such as outreach, training, and assistance in law enforcement. The results of this community service show that community participation in the law enforcement process can increase effectiveness and efficiency in law enforcement efforts. In addition, community involvement increases awareness of human rights and the importance of maintaining public order and security. Even so, some obstacles are encountered in implementing this community service, such as the lack of support from the authorities, the lack of public access to information, and the community's lack of understanding of the legal system. Therefore, further efforts are needed to increase community participation in law enforcement and overcome the obstacles they face.